A Unified System Modelling and Programming Language based on JavaScript and a Semantic Type System - Bosse, Stefan (Procedia manufacturing, 2018)
The design and simulation of complex mechatronic and intelligent systems require a unified system modelling and programming language. This work introduces JavaScript as a unified modelling and programming language by extending JavaScript with a semantic type system extension JST as a possible solution to fill the gap between models and implementations, finally resulting in the JS+ super set language combining typing, modelling, and programming. The paper shows various model domains and their relation to the JS+ programming model including some generic transformation rules. Finally, a system compiler framework is introduced that can process JS+ models and program code. The tool uses JS+ input to produce a wide range of output formats for software and hardware design, and multi-domain simulation.